Double-Front Crystallization in the Chapesvara Ultramafic Subvolcanic Complex, Serpentinite Belt, Kola Peninsula, Russia - Andrei Y. Barkov; Vladimir N. Korolyuk; Larisa P. Barkova; Robert F. Martin (Minerals, 2019)
Dunite–harzburgite–olivine-bearing orthopyroxenite successions in the subvolcanic Chapesvara-I and Chapesvara-II intrusions in the Serpentinite Belt, western Kola Peninsula, are notably magnesian. The mean Mg# value (whole-rock) is 86.6, and the olivine is Fo84−89. The upper contact facies (UCF) displays a lower Mg# (81.6). It consists of grains of Fo92 and abundant chromian spinel, implying rapid crystallization of an almost unfractionated melt. On average, the whole-rock Al2O3/TiO2 value is 22.45, close to 22.9 (UCF) and to the primitive mantle, ~22. The rise of primitive ultramafic magma presumably occurred in a special tectonic setting at the boundary of the Paleoproterozoic Lapland Granulite Terrane and the Belomorian Composite Terrane of Archean age. The Chapesvara suite resembles examples of the Al-undepleted komatiites in the Barberton Belt, South Africa, with magmas of up to 30–35% MgO. The UCF rock yields an anomalously low molar MgO/SiO2 value, close to that of dunitic rocks located at the center of the Chapesvara-II body. This rock is the most primitive, as indicated by the maximum Fo content of olivine, the lowest value of (Gd/Yb)N, 0.52, and the lowest abundances of middle to heavy rare-earth elements (REE) in the chondrite-normalized spectrum. The crystallization of the Chapesvara-II sill-like intrusion likely proceeded in two stages, which are evident from the olivine compositions varying from the maximum Fo92 (UCF) to Fo≤89.5 (the central dunite zone). At Stage 1, the UCF rock (Fo92) crystallized first, close to the upper contact. The area of crystallization then shifted to a central portion of the Chapesvara-II body, in which the dunitic zone (Fo89.5) formed in situ (Stage 2). The compositional variations in chromian spinel are consistent with this suggestion. Two crystallization trends were recognized. The type-1 trend displays a relative maximum or minimum close to the center, and then diverges into two linear subtrends directed upward and downward. This pattern is manifested in the ...